Hope by Candlelight Memorial for suicide loss is Oct. 1 - Uribes, Tom::::::::: (2013)
Hope by Candlelight,' a vigil in remembrance of those lost to suicide, will be held 5:30 p.m., Tuesday, Oct.1 in the Fresno State Peace Garden.